City Worms (Onychophora): why do fragile invertebrates from an ancient lineage live in heavily urbanized areas? (UNED Research Journal, 2018)
Velvet worms, fragile invertebrates from an ancient lineage, are prone to extinction because of their small populations, low vagility and limited geographic ranges. However, I found that 19 species, nearly all of them Latin American and Caribbean peripatids, have been reported from heavily urbanized areas. Onychophoran worms lack most of the characteristics of successful urban animals, but I hypothesize that they survive in cities because diet and undetectability favor them. Citizen scientists could help with the urgent need of learning more about urban onychophorans.
Keywords: Urban fauna; effects of urbanization; living fossils; Onychophora